Understanding Marawi’s Media Landscape for Peace and Sustainable Development - Latip-Yusoph, Sorhaila (International Journal of Global Sustainable Research, 2024)
This study examines Marawi City's media landscape before, during, and after the 2017 siege, investigating existing outlets, media practitioner dynamics/safety challenges, and media's role in peacebuilding and sustainable development. Findings reveal a pre-siege thriving local press transitioning to intense national/international coverage during the siege, with local voices emerging through initiatives like "S'bang Ka Marawi" radio program. Post-siege saw a local radio revival alongside social media's rise, posing trust and literacy issues. The Meranaw language is preferred but lacks a standardized orthography. Local journalists face capacity gaps in training and safety resources. Recommendations include revitalizing local media, promoting media literacy alongside Meranaw language standardization, and investing in media safety training. Further studies are proposed on social media's impact on trust/information sharing, comparative pre/post-siege media consumption analysis, and examining local media's peacebuilding role.